Effect of hydrogen on the corrosion behavior of the Mg–xZn alloys - Yingwei Song; En-Hou Han; Kaihui Dong; Dayong Shan; Chang Dong Yim; Bong Sun You (Journal of Magnesium and Alloys, 2014)
Hydrogen evolution reaction is inevitable during the corrosion of Mg alloys. The effect of hydrogen on the corrosion behavior of the Mg–2Zn and Mg–5Zn alloys is investigated by charging hydrogen treatment. The surface morphologies of the samples after charging hydrogen were observed using a scanning electron microscopy (SEM) and the corrosion resistance was evaluated by polarization curves. It is found that there are oxide films formed on the surface of the charged hydrogen samples. The low hydrogen evolution rate is helpful to improve the corrosion resistance of Mg alloys, while the high hydrogen evolution rate can increases the defects in the films and further deteriorates their protection ability. Also, the charging hydrogen effect is greatly associated with the microstructure of Mg substrate.